2016
DOI: 10.1111/jcmm.12932
|View full text |Cite
|
Sign up to set email alerts
|

Equine metabolic syndrome impairs adipose stem cells osteogenic differentiation by predominance of autophagy over selective mitophagy

Abstract: Adipose‐derived mesenchymal stem cells (ASC) hold great promise in the treatment of many disorders including musculoskeletal system, cardiovascular and/or endocrine diseases. However, the cytophysiological condition of cells, used for engraftment seems to be fundamental factor that might determine the effectiveness of clinical therapy. In this study we investigated growth kinetics, senescence, accumulation of oxidative stress factors, mitochondrial biogenesis, autophagy and osteogenic differentiation potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
63
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 87 publications
1
63
0
Order By: Relevance
“…It is tempting to speculate that similar, paradox, mechanism is switched on in EMS horses, standing as an adaptation to help animals maintain their metabolic help. Moreover, feeding mice on high-fat diet accelerated FGF21 beneficial effect; thus activating FGF21 by deteriorated mitochondria may be indeed the protective mechanism in individuals suffering from diabetes and metabolic syndrome, especially the fact that mitochondrial dysfunction in both of these diseases was proved in many studies [10, 3133]. …”
Section: Discussionmentioning
confidence: 99%
“…It is tempting to speculate that similar, paradox, mechanism is switched on in EMS horses, standing as an adaptation to help animals maintain their metabolic help. Moreover, feeding mice on high-fat diet accelerated FGF21 beneficial effect; thus activating FGF21 by deteriorated mitochondria may be indeed the protective mechanism in individuals suffering from diabetes and metabolic syndrome, especially the fact that mitochondrial dysfunction in both of these diseases was proved in many studies [10, 3133]. …”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis may be supported by PARKIN knockdown, which resulted in the down‐regulation of RUNX and Coll‐1; this in turn underlines its role in the course of osteogenic differentiation. Our previous research demonstrated that ASC EMS had impaired mitophagy, as decreased PGC1α, PARKIN and PDK4 activities together with reduced osteogenic differentiation potential were recorded 28. Thus, the obtained data indicate that pre‐treatment of ASC EMS with AZA/RES enhances osteogenic properties of these cells via increased mitophagy.…”
Section: Discussionmentioning
confidence: 58%
“…It was demonstrated that excessive accumulation of OS factors, ie ROS and NO, together with significantly decreased antioxidant protection, might be associated with reduced osteogenic differentiation potential and extracellular matrix formation 28, 33. In turn, many studies including ours, have shown that RES significantly attenuates OS by modulating SOD activity and mitochondrial dynamics 34, 35, 36.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations